After the deluge: mining Staphylococcus aureus genomic data for clinical associations and host–pathogen interactions. (February 2018) - Copin, Richard; Shopsin, Bo; Torres, Victor J
Highlights: Whole-genome sequencing has enabled real-time genomic surveillance of S. aureus . Of the 40, 000 available S. aureus genomes in NCBI only 0.4% are fully assembled. S. aureus genomic heterogeneity encompasses mutation and mobile genetic elements. Long-read sequencing is required to capture mobile genetic element diversity. Methods for accurately annotating of S. aureus genomes are desperately needed. Abstract : The genome of Staphylococcus aureus has rapidly become one the most frequently sequenced among bacteria, with more than 40 000 genome sequences uploaded to public databases. Computational resources required for analysis and quality assessment have lagged behind accumulation of sequence data. Improved analytic pipelines, in combination with the development of customized S. aureus reference databases, can be used to inform S. aureus biology and potentially predict clinical outcome. Here, we review the currently available data about S. aureus genome in public databases, and discuss their potential utility for understanding S. aureus evolution. Also discussed are ways to overcome challenges to the application of whole-genome sequencing data for prevention and management of S. aureus disease.